Oral Administration of Caesalpinia bonducella Seeds Ethanolic Extract Decreased Post Prandial Blood Glucose Level and Prevented the Reduction of Fasting Insulin Level of Diabetic Male Albino Rats (Rattus norvegicus) - Veny Larasati; Wimpie Pangkahila; Anak Agung Gde Budhiarta (JURNAL KEDOKTERAN DAN KESEHATAN, 2016)
Caesalpinia bonducella contain flavonoid, tanin, saponin which has antidiabetic activity.  The aim of this study was to determine that the Caesalpinia bonducella seed extract orally reduces post-prandial blood glucose level and prevent the reduction of fasting insulin level in diabetic male albino rats (Rattus norvegicus). This study was a true experimental with pre-test post-test control group design using 24 male albino rats.  All samples were induced with streptozotocin which caused the destruction of ? cell and nicotinamide which protected the ? cell from destructions of that the pancreatic ?-cell was not destructed entirely. The selected samples were divided into three groups: the control negative group was given distilled water (P0), the control positive group was given glibenclamide (P1), and the treatment group was given ethanolic extracts of Caesalpinia bonducella seed 500mg/kg body weight (P2).  Blood glucose and plasma insulin measurements were taken after 14 days of treatment. The result showed that the post-prandial blood glucose level of treatment group (P2) was decreased significantly, from 232,63±10,31 mg/dl to 185,50±16,00 mg/dl (P<0.001) whereas in P0 group, post-prandial blood glucose level was rising significantly from 223,75±17.03 mg/dl to 267,25±17,56 mg/dl (p<0.001). In P1 group, the reduction of post-prandial blood glucose level was bigger compare to P2 group, which was from 228,50±11,55 mg/dl to 115,88±10,23 mg/dl (p<0.001).  Post test fasting insulin level of P2 group was significantly different compare to other group (p<0.05). The administration of Caesalpinia bonducella seed extract increased the fasting insulin level although did not significant statistically (p>0.05) whereas the other group showed the reduction of fasting insulin level (p<0.05). It can be concluded that the administration of Caesalpinia bonducella seed extract orally reduced post-prandial blood glucose level and prevent reduction of fasting plasma insulin level in diabetic male albino rats.